Utility of Colour Flow Doppler Ultrasonography to Differentiate Gestational Transient Thyrotoxicosis and Graves Disease in Pregnancy - Danda, Vijay Sheker Reddy; Lodha, Piyush; Paidipally, Srinivas Rao; Devireddy, Sandeep Reddy (Indian journal of endocrinology and metabolism, 2024)
Abstract Introduction: Accurate diagnosis of the etiology of thyrotoxicosis in pregnancy is important to guide appropriate treatment. The role of thyroid blood flow velocities by color Doppler to differentiate between Graves' disease (GD) in pregnancy and gestational transient thyrotoxicosis (GTT) is not well explored. This study evaluated inferior thyroid artery (ITA)-peak systolic velocity (PSV) as a marker for differential diagnosis of thyrotoxicosis in pregnancy. Methods: Fifty-six pregnant patients with thyrotoxicosis (30 with GTT and 26 with GD) along with 30 age-matched healthy euthyroid pregnant subjects were enrolled. Thyroid ultrasound examinations and color Doppler was performed by an ultrasound scanner. The studies of the right and left ITAs were performed with Doppler, and the PSV and End diastolic velocity (EDV) values were obtained from the right and left ITA. Results: The mean total T4 value in GD and GTT were almost similar (25.04 ± 2.43 vs 23.25 ± 2.81, P value = 0.14). Beta HCG levels were significantly higher in cases of GTT as compared to GD (152946 ± 26694 vs 120608 ± 21244 mIU/ml, P < 0.0001). The ITA-PSV and EDV in patients with GTT were significantly lower than those of pregnant patients with GD (right: 22.5 ± 6.8 and 8.3 ± 2.3; left: 22.97 ± 6.3 and 8.13 ± 2.01; P < 0.001). receiver-operating-characteristic (ROC) curve demonstrated an optimal cutoff value of mean right ITA-PSV of 35 cm/sec to differentiate GTT from GD during pregnancy, with 84.6% and 93.3% sensitivity and specificity. Conclusion: Thyroid artery velocities can help to differentiate between GD and GTT. The cutoff point of mean ITA-PSV at 35 cm/s had an excellent value in differentiating between the two, with good sensitivity and specificity.